Predictive biomarkers for targeted therapy in daily anatomic pathology for ovarian tumors - Niti Sureka; Sufian Zaheer (Surgical and Experimental Pathology)
Abstract Predictive biomarkers have transformed the landscape of ovarian cancer management, facilitating precision oncology and enabling the delivery of therapies tailored to the genetic and molecular profiles of individual tumors. Ovarian cancer, characterized by substantial heterogeneity, benefits from advances in molecular diagnostics that allow clinicians to stratify patients effectively. Key biomarkers such as BRCA1/2 mutations and homologous recombination deficiency (HRD) have guided the clinical application of poly(ADP-ribose) polymerase inhibitors (PARPi), which exploit synthetic lethality in tumor cells. Similarly, mismatch repair deficiency (MMRd) and microsatellite instability (MSI) have expanded therapeutic options by identifying candidates for immune checkpoint inhibitors. Emerging biomarkers like programmed death-ligand 1 (PD-L1) expression and angiogenesis markers such as VEGF further enhance therapeutic strategies, paving the way for combination treatments in refractory and relapsed cases. The integration of next-generation sequencing (NGS) and liquid biopsies into routine diagnostics underscores the dynamic nature of biomarker discovery, offering opportunities to monitor tumor evolution and therapeutic response. This review provides an in-depth exploration of the current and emerging predictive biomarkers in ovarian cancer, emphasizing their clinical implications and potential to improve patient outcomes.